An Ultrahigh Sensitivity Microwave Sensor for Microfluidic Applications - Fan, Li-Chao; Zhao, Wen-Sheng; Wang, Da-Wei; Liu, Qi; Chen, Shichang; Wang, Gaofeng (IEEE microwave and wireless components letters, 2020)
This work shows an ultrahigh sensitivity microwave sensor for microfluidic applications. The proposed sensor is made of a microstrip line loaded with a complementary splitring resonator (CSRR). The meander slot is adopted in the CSRR to achieve high field confinement and is therefore covered with a polydimethylsiloxane (PDMS) microfluidic channel to enable strong interaction between the field and the liquid sample. The complex permittivity of the liquid sample can be retrieved by the variations in the resonant frequency and peak attenuation. The proposed design requires a very small liquid volume of ~0.5 μL while offering a high sensitivity. A prototype is fabricated and tested, with a good agreement achieved between the extracted values and the reference data.